Peran Akreditasi Dalam Peningkatan Mutu Sekolah Di Mi Cimahi Pentas - Jimmi Kurniawan; Roni Rahman; Siti Qomariyah; Andi Sukandi (Jurnal Budi Pekerti Agama Islam, 2024)
Evaluation of education quality is important because good quality education ensures that students receive relevant, in-depth and meaningful education. Accreditation is an evaluation process carried out by educational authority institutions or independent bodies to assess the quality of an educational institution. This research aims to determine the effect of implementing accreditation on improving the quality of education at MI Cimahi Peuntas. This research was conducted using a descriptive qualitative approach. Based on the results obtained, MI Cimahi Pentas is trying to carry out follow-up actions to improve school quality, namely: (1) Improving the implementation of quality school management, starting from planning, implementing, organizing, monitoring and evaluating education and learning activities and supporting education and learning activities in school; (2) The accreditation results and recommendations obtained are used as material for consideration by the school in the context of making policies to improve school quality; and (3) Improving technology-based school facilities and infrastructure to support education and learning activities in schools.